Common fault effects on a natural refrigerant, variable-speed heat pump. (January 2022) - Bellanco, I.; Belío, F.; Vallés, M.; Gerber, R.; Salom, J.
Highlights: Experimental fault tests on a variable-speed heat pump charged with propane. Experimental procedure to emulate evaporator fouling, compressor valve leakage, liquid line restriction and refrigerant overcharge. Quantitative results of the fault effects for two different heat demands. Trend chart of relevant features of the heat pump. Abstract: The European heat pump market is growing every year as European legislation moves towards the use of natural refrigerants that have less global warming potential than conventional refrigerants. Even though heat pumps are very efficient, the appearance of hard-to-detect faults increases energy consumption. The present study emulated some of the most common faults on a variable-speed heat pump charged with propane. The faults tested were evaporator fouling, compressor valve leakage, liquid line restriction and refrigerant overcharge. The effect of these faults on performance and several heat pump features are described. Evaporator fouling was the fault with least COP degradation and compressor valve leakage with the most (7% and 56% COP reduction, respectively). The results are compared with the results from a comparable study. The heat pump covered the demand generated by nearly all the faults at the expense of increasing the power consumption. The features of each fault are summarized in a chart, which could be used as table for diagnosing faults.